Effect of Financial Performance on Dividend Policy in Manufacturing Companies in Indonesia Stock Exchange - Delfian Rian Zaman (Integrated Journal of Business and Economics (IJBE), 2018)
This study aims to examine the effect of cash ratio, debt to equity ratio, and return on the asset to dividend payout ratio on manufacturing companies listed on Indonesia Stock Exchange with observation period 2010-2014. The sampling technique used is purposive sampling so that the number of samples is 27 companies. The analysis technique used in this research is multiple linear regression and hypothesis test using t-statistic to test partial regression coefficient and f-statistic to test the feasibility of research model with a level of significance 5%. Besides, there is also a classic assumption test that includes normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. The result of the analysis shows that the variable of cash ratio and return on asset have positive and significant influence, while the variable of debt to equity ratio has a negative and significant effect to dividend payout ratio.